Factors for successful e-learning: does age matter?. Issue 1 (9th January 2017) - Fleming, Julie; Becker, Karen; Newton, Cameron
Abstract : Purpose: The purpose of this paper is to examine the factors affecting employees' overall acceptance, satisfaction and future use of e-learning, specifically exploring the impact that age has on the intended future use of e-learning relative to the other potential predictors. Design/methodology/approach: The project developed an online survey and invited employees of one Australian rail organisation to participate. Questions were structured around the factors that affect acceptance and future use of e-learning. Statistical analysis was used. Findings: The findings from the study suggest that, despite the often espoused stereotype, age is not a significant factor impacting either future use intentions or satisfaction with e-learning. In contrast, three variables were found to be useful predictors of intention for future use of organisational e-learning; low complexity, authenticity and technical support. Research limitations/implications: The study did not consider other moderating effects related to demographic data other than age, such as educational experience. Further, the case presented is a single organisation and therefore is not necessarily representative of other industries. Future studies should adopt a mixed methods approach. Practical implications: This study has emphasised that attention needs to be focussed on factors over which organisations have control when adopting and using e-learning. Employee age should not be seen as an obstacle to e-learning implementation, rather attention needs to turn to effective and user-friendly e-learning interventions along with sufficient technology support. Originality/value: Perceptions within industry and indeed in some literature, suggest that employee age stereotypes still exist in relation to technology uptake. This research has demonstrated that this stereotype is an erroneous assumption and emphasised the importance of other factors.